1990
DOI: 10.1111/j.1365-2796.1990.tb00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Low plasma concentrations of atrial natriuretic peptide in untreated hypothyroid patients

Abstract: A group of patients with primary hypothyroidism has been studied, and it is reported that low serum levels of thyroid hormones are accompanied by low plasma atrial natriuretic peptide (ANP) concentrations. While the correlation between ANP and thyroid hormone levels is strong, no correlation was found between ANP and heart rate or arterial blood pressure. It is suggested that thyroid hormones directly stimulate the release of ANP from atrial cardiocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The finding that hypothyroid patients in our study did not show lower plasma ANH levels, such as observed in previous studies (15,16), may be related to the degree of the disease, which in our patients was mild (8). How¬ ever, in other reports plasma ANH values in hypothyroid patients did not differ from normals (10) or actually increased (9).…”
Section: Discussionsupporting
confidence: 78%
“…The finding that hypothyroid patients in our study did not show lower plasma ANH levels, such as observed in previous studies (15,16), may be related to the degree of the disease, which in our patients was mild (8). How¬ ever, in other reports plasma ANH values in hypothyroid patients did not differ from normals (10) or actually increased (9).…”
Section: Discussionsupporting
confidence: 78%
“…The principal cause of the discrepancies may be differences in the severity of the hypothyroidism, with significant differences only in the patients with serious deficit, as suggested by Kohno et al (1987). The duration of the hypothyroidism could also influence the plasma ANH levels of these patients, although Widecka et al (1990) found differences after only a short period of levothyroxine withdrawal. In our study, as in all those in which the hypothyroid patients have been diagnosed recently and have not received treatment, the real duration of the disease is unknown.…”
Section: Discussionmentioning
confidence: 69%
“…In patients with hypothyroidism, plasma ANH concentrations have been reported to be low (Kohno et al 1987, Zimmerman et al 1987, Woolf & Moult 1988, Widecka et al 1990, Barna et al 1994, Ota et al 1994 or normal (Ladenson et al 1987, Rolandi et al 1992. After thyroid replacement these concentrations have increased in some reports (Kohno et al 1987, Zimmerman et al 1987, Woolf & Moult 1988, Rolandi et al 1992, Bernstein et al 1997 but not in others (Weissel et al 1986, Ladenson et al 1987.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, it is possible that the release of ANP, eliciting diuresis and natriuresis, may be impaired in the hypothyroid state, thereby resulting in impairment of renal water and electrolytes excretion, irrespective of AVP release. Indeed, ANP release as well as its synthesis has been reported to be impaired in hypothyroid states [17][18][19][20]. Thirdly, the possibility is not ruled out that a decrease in plasma volume may occur in the hypothyroid state, irrespective of plasma AVP and ANP, thereby stimulating the proximal tubular reabsorption of water and sodium and causing decreased CH 2u formation.…”
Section: Discussionmentioning
confidence: 99%